1994
DOI: 10.1002/pro.5560030908
|View full text |Cite
|
Sign up to set email alerts
|

Thermal unfolding of tetrameric melittin: Comparison with the molten globule state of cytochrome c

Abstract: Whereas melittin at micromolar concentrations is unfolded under conditions of low salt at neutral pH, it transforms to a tetrameric a-helical structure under several conditions, such as high peptide concentration, high anion concentration, or alkaline pH. The anion-and pH-dependent stabilization of the tetrameric structure is similar to that of the molten globule state of several acid-denatured proteins, suggesting that tetrameric melittin might be a state similar to the molten globule state. To test this poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
27
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 49 publications
9
27
1
Order By: Relevance
“…We carefully chose neutral quenchers so as to avoid any specific interaction with the quencher and melittin since this peptide possesses +6 and +24 charges in its monomer and tetramer forms, respectively. 47 Acrylamide is a widely used neutral aqueous quencher of tryptophan fluorescence. Acrylamide quenching of tryptophan fluorescence is widely used to monitor tryptophan environments in proteins and peptides.…”
Section: Quenching Of Melittin Tryptophan Fluorescencementioning
confidence: 99%
“…We carefully chose neutral quenchers so as to avoid any specific interaction with the quencher and melittin since this peptide possesses +6 and +24 charges in its monomer and tetramer forms, respectively. 47 Acrylamide is a widely used neutral aqueous quencher of tryptophan fluorescence. Acrylamide quenching of tryptophan fluorescence is widely used to monitor tryptophan environments in proteins and peptides.…”
Section: Quenching Of Melittin Tryptophan Fluorescencementioning
confidence: 99%
“…Temperaturedependent NMR studies have shown that upon heating the positions of the melittin monomers inside the tetramer differ from those in the crystal structure 7 and that the hydrophobic residues of melittin in solution are probably more exposed than in the crystal. 8 The symmetry of the tetramer structure suggests that melittin can also form dimers in solution and that selfassociation into a tetrameric state is a two-step reaction. However, stable melittin dimers have never been identified, 9 and the self-association process is usually described as one process in which four melittin monomers associate toward one tetrameric state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]8,9,10 The self-association process of melittin is accompanied by a blue shift of the Trp fluorescence maximum due to shielding of the Trp residues in a hydrophobic pocket and can be observed by steady-state fluorescence measurements. Time-resolved magic-angle fluorescence and anisotropy measurements provide information about the Trp environment and the mobility of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…The ccd system was the first one to be identified (6) and remains the best studied. The ccd operon encodes a toxin (CcdB: 101 amino acids, 11.7 kDa) and its antidote (CcdA: 72 amino acids, 8.3 kDa).…”
mentioning
confidence: 99%